2003
DOI: 10.4049/jimmunol.170.9.4524
|View full text |Cite
|
Sign up to set email alerts
|

IL-7-Regulated Homeostatic Maintenance of Recent Thymic Emigrants in Association with Caspase-Mediated Cell Proliferation and Apoptotic Cell Death

Abstract: Homeostasis of T cells is essential to the maintenance of the T cell pool and TCR diversity. In this study, mechanisms involved in the regulation of cytokine-mediated expansion of naive T cells in the absence of Ag, in particular the role of caspase activation and susceptibility to apoptosis of recent thymic emigrants (RTEs), were examined. Low level caspase-8 and caspase-3 activation was detected in proliferating IL-7-treated cells in the absence of cell death during the first days of culture. Caspase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…We also demonstrated that the antiproliferative effect of CO in airway smooth muscle cells is mediated by the extracellular signal-regulated kinase MAPK pathway (13). Most of the biological effects attributed to CO including anti-inflammatory, antiapoptotic, and now antiproliferative effects have been linked to its ability to modulate the activity of guanylate cyclase and to increase the levels of cellular cGMP (7,14,25,26,28,33,34) and/or the MAPK pathways such as p38 or extracellular signalregulated kinase.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We also demonstrated that the antiproliferative effect of CO in airway smooth muscle cells is mediated by the extracellular signal-regulated kinase MAPK pathway (13). Most of the biological effects attributed to CO including anti-inflammatory, antiapoptotic, and now antiproliferative effects have been linked to its ability to modulate the activity of guanylate cyclase and to increase the levels of cellular cGMP (7,14,25,26,28,33,34) and/or the MAPK pathways such as p38 or extracellular signalregulated kinase.…”
Section: Discussionmentioning
confidence: 93%
“…Low-level caspase-8 and caspase-3 activation was detected in proliferating IL-7-treated cells in the absence of cell death during the first days of culture (34). Caspase inhibitors suppressed IL-7-induced expansion of recent thymic emigrants (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral expansion can be evidenced by the large reduction in TREC content in the naive CD4 ϩ T cell pool during aging (3,13). Although the mechanism by which peripheral expansion occurs is not entirely elucidated, in vivo murine studies have pointed to low-affinity TCR binding as a potential inducer of naive T cell replication (14 -16), and in vitro human studies have found that IL-7 and various other cytokines can stimulate naive T cell division without loss of naive phenotype (17)(18)(19).…”
mentioning
confidence: 99%
“…The T-cell receptors utilised by RTE are structurally different to those on mature naive or memory T-cells [28], and facilitate promiscuous low affinity reactions to a wide range of peptides, triggering an initial burst of cytokine production followed by rapid apoptosis, in some cases accompanied by bystander activation of regulatory T-cells [27]. As these RTE progressively die out during early childhood, they are presumably We believe that the responses are allergen specific, although the allergen extracts are not endotoxin free, since we have earlier reported that immune responses to birch extract are related to birch allergy [11] and that cells from birch or cat sensitised children respond with Th2 like cytokine production after stimulation with birch or cat allergen extract, but not after stimulation with an unrelated allergen [4].…”
Section: Ethicsmentioning
confidence: 99%